Evaluation Program Of Subject Teacher Working Group And Information Technologi Workshop At SMK Negeri 2 Toraja Utara - Rita, Nobe Bara’; Sihotang, Hotmaulina; Murniarti, Erni (Advances in Social Sciences Research Journal, 2020)
The urgency of improving teachers’ competences is behind the reason of teachers forum and workshop in education. However, every program should be evaluated to find out whether the program has reached its goal. This study puts its purpose on first, seeing whether the programs subject teacher working group increasing the competence of teachers in SMKN 2 Toraja Utara, especially in professional competence. The second is to give informations that contribute to programs improvement. The evaluation model that is used is contex, input, procces and product (CIPP) model which evaluate a program in four aspects: context, input, process and product. Data were collected through observation, questionnaire, interview, school document and program documents. The finding is the programs (teacher forum and workshop) categorized satisfactory and still need improvement in rules, materials, learning strategy, time, facilities and teachers motivation should be improved.